2015
DOI: 10.5665/sleep.4582
|View full text |Cite
|
Sign up to set email alerts
|

Psychiatric Comorbidity and Cognitive Profile in Children with Narcolepsy with or without Association to the H1N1 Influenza Vaccination

Abstract: Our study indicates increased psychiatric comorbidity in children and adolescents with narcolepsy. The identified cognitive profile with significantly lower verbal comprehension and working memory compared with the normal mean index could have important implications for social relations and schooling. The small numbers of patients with nPHV narcolepsy make it difficult to draw firm conclusions about the possible differences between the two groups of patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
64
2
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(72 citation statements)
references
References 40 publications
5
64
2
1
Order By: Relevance
“…Reasons for this remain somewhat unclear. A more sudden onset and severe symptoms in pNT1 than in sporadic narcolepsy type 1 (NT1) could be an explaining factor [5,6]. On the other hand, a comparison between Finnish children with pNT1 and Italian children with NT1 appears to show similar clinical pictures, although subjects with pNT1 often had increased nocturnal sleep disturbance [14].…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Reasons for this remain somewhat unclear. A more sudden onset and severe symptoms in pNT1 than in sporadic narcolepsy type 1 (NT1) could be an explaining factor [5,6]. On the other hand, a comparison between Finnish children with pNT1 and Italian children with NT1 appears to show similar clinical pictures, although subjects with pNT1 often had increased nocturnal sleep disturbance [14].…”
Section: Introductionmentioning
confidence: 98%
“…The main symptoms of narcolepsy are excessive daytime sleepiness, disturbed nocturnal sleep, cataplexy, sleep paralyses, and hallucinations during sleep-wake transitions. Other common associated features are increased weight, precocious puberty, behavioral problems, and psychiatric comorbidity [4][5][6]. There is a great heterogeneity in symptoms as some subjects are severely affected and disabled, whereas others manage without medication.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, up to 7% of all patients with a diagnosis of schizophrenia may have a psychotic variant of narcolepsy [1]. Conversely, psychotic symptoms of comorbid schizophrenia may forerun or present along the course of narcolepsy type 1 (NT1) [6,7,8,9,10]. The failure to distinguish narcolepsy leads to the labeling of patients as refractory to standard treatments for schizophrenia and delays the consideration of specific intervention for narcolepsy.…”
Section: Introductionmentioning
confidence: 99%
“…The four (20%) studies that looked at the intellectual implications of a hypersomnolence disorder all used one of the Wechsler assessments to determine intellectual functioning, with verbal IQ (VIQ) and nonverbal IQ (NVIQ) also reported. Two of the four studies (Dorris et al, 2008;Posar et al, 2014) were case studies employing standardised assessments that yielded quantitative data that resulted in individual rather than group The two studies (Szakács, 2016;Szakács et al, 2015) which were conducted with larger groups of children and adolescents with narcolepsy also found that most subjects had a FSIQ in the average range, with a number having a FSIQ in the gifted range. These studies investigated groups of 38 and 37 participants respectively, allowing some generalisability of results.…”
Section: Intellectual Functioning and Hypersomnolencementioning
confidence: 99%
“…In all seven studies, the EF and hypersomnolence association was irregularly explored with inconsistent methodologies, multiple definitions of EF, and numerous choices of assessment instruments. These included subtests from the Wechsler scales (Hansen, 1997;Ito et al;Szakács, 2016;Szakács et al, 2015), Wakefulness Test (MWT). This was used to identify vigilance.…”
Section: Executive Functioning and Hypersomnolencementioning
confidence: 99%